Improvement of the outcome of the saphenous vein graft when connected to the internal thoracic artery - Katsavrias, Konstantinos; Prapas, Sotirios; Calafiore, Antonio M.; Taggart, David; Angouras, Dimitrios; Iliopoulos, Dimitrios; Di Mauro, Michele; Papandreopoulos, Styliani; Zografos, Panayiotis; Dougenis, Dimitrios (Frontiers in Cardiovascular Medicine, 2024)
Background. Since 2000, we have been grafting the right coronary artery system (RCAs) using the proximal portion of the right internal thoracic artery (RITA) as the inflow of the saphenous vein graft (SVG) to increase the number of patients undergoing beating heart complete myocardial revascularization. Methods. From 2000 to 2022 928 consecutive patients underwent SVG on RCAs. In 546 cases (58.8%) the inflow was the RITA (I-graft group), in 382 (41.2%) the aorta (Ao-graft group). Inclusion criteria were age ≤75 years, ejection fraction ≤>35%, only one SVG per patient, bilateral internal thoracic arteries as a Y graft on the left system (3-vessel disease, n=817, 88.0%) or left internal thoracic artery on left anterior descending artery and RITA+SVG on the RCAs (2-vessel disease, n=111, 12.0%). Propensity matching identified 306 patients per group. After a median follow-up of 8(5-10) years, graft patency was assessed by coronary computed tomographic angiography in 132 patients (64 in I-graft group and 68 in Ao-graft group). Results. Early results were similar in both groups. The I-graft group had higher 10-year survival and freedom from main adverse cardiac events (90.0±2.0 vs 80.6±3.8, p=0.0162, and 81.3±2.7 vs 64.7±5.6, p=0.0206, respectively). When RITA was the inflow, SVG had a higher estimated 10-year patency rate (82.8%±6.5 vs 58.8%±7.4, p=0.0026) and a smaller inner lumen diameter (2.7±0.4 vs 3.4±0.6 mm, p<0.0001). Conclusion. When the inflow is the RITA, SVG grafted to the RCAs (I-graft) may result in a higher patency rate and better outcome than when the inflow is the ascending aorta (Ao-graft). The continuous supply of nitric oxide by RITA may be the cause of the higher patency rate of the I-graft which can behave like an arterial conduit.